Strategy Analyses Study For Evaluating Sport Activities on University of Baghdad Colleges - Daher, Sahira Flaih Mohameed (Journal of Physical Education, 2021)
The research aimed at identifying the results of strategic analyses for evaluating sports activities as well as identifying the differences between scientific and humanity colleges and their role in sports activities. The subjects were (54) faculty members in students activity/ sport activities in (17) colleges affiliated with the University of Baghdad. The results showed a lack of interest in sports activities as well as administrative obstacles that hinder students’ participation in sports events. Finally, the researcher recommended the necessity of encouraging students to participate in sports activities and increasing the university’s financial support.